Tribological performance of palmitic acid as lubricant additives for rotary compressor / Abdul Halim Ahmad - Abdul Halim, Ahmad (2014)
Nowadays petroleum based lubricants demand is high compared to vegetables based lubricant due to increasing of industrialization, modernization and development. Due to easy oxidization and poor lubricating performance at high temperature, therefore vegetables based lubricants has not been widely used in industrial application. However, long fatty acid chains contained in it may significantly reduce coefficient of friction (COF) and wearing rate of rubbing metal surface. Lubrication optimization can be achieved by the addition of vegetable oils as additives in mineral oil. In this paper, three rotary compressor oils which is Suniso, Polyolester (POE) and Polyvinylether (PVE) will be mixed with palmitic acid which is one of the most widely produced fatty acid. The purpose of the study is to investigate the tribological performance of the oil when added with fatty acid additives. Testing was conducted using four-ball tester machine in accordance to ASTM standard D4172. The base oil will be mixed in a different percentage of palmitic acid and tested accordingly. The result shows that palmitic acid effectively performed as lubricant additives in Suniso and POE oil to reduce frictional torque and coefficient of friction (COF). Significant impact in wear scar diameter improvement can only be observed in Suniso oil and palmitic acid mixture. PVE oil which is added with palmitic acid shows the result of increasing in flash temperature value which made it possible to improve performance of PVE oil at very high temperature applications. Based on the result it can be concluded that palmitic acid as additives may effectively applicable to Suniso and POE oil. On the other hand, applications which require higher operating temperature should consider using PVE oil mix with palmitic acid to increase the flash temperature value.